LPA/PKD-1-FoxO1 Signaling Axis Mediates Endothelial Cell CD36 Transcriptional Repression and Proangiogenic and Proarteriogenic Reprogramming. Issue 6 (June 2016) - Ren, Bin; Best, Brad; Ramakrishnan, Devi Prasadh; Walcott, Brian P.; Storz, Peter; Silverstein, Roy L.
Abstract : Objective—: CD36 is a scavenger and antiangiogenic receptor that is important in atherothrombotic diseases, diabetes mellitus, cancer, and obesity. Lysophosphatidic acid, a phospholipid signaling mediator, abolishes endothelial cell responses to antiangiogenic proteins containing thrombospondin type 1 homology domains by downregulating endothelial CD36 transcription via protein kinase D1 (PKD-1) signaling. We aimed to understand mechanisms by which lysophosphatidic acid–mediated angiogenic signaling is integrated to regulate CD36 transcription and endothelial cell function via a nuclear transcriptional complex. Approach and Results—: Microvascular endothelial cells expressing CD36 were used for studying angiogenic signaling and CD36 transcription. Gene transfection and transduction, RT-qPCR, avidin–biotin-conjugated DNA-binding assay, chromatin immunoprecipitation assay, co-immunoprecipitation, proximal ligation assay, and immunofluorescence microscopy showed that lysophosphatidic acid–mediated CD36 transcriptional repression involved PKD-1 signaling mediated formation of forkhead box protein O1–histone deacetylase 7 complex in the nucleus. Unexpectedly, turning off CD36 transcription initiated reprogramming microvascular endothelial cells to express ephrin B2, a critical molecular signature involved in angiogenesis and arteriogenesis. Spheroid-based angiogenesis and in vivo Matrigel angiogenesis assays indicated that angiogenic branching morphogenesis and in vivo angiogenesis were dependent on PKD-1 signaling. A mouse tumor angiogenesis model revealed enhanced PKD-1 signaling and expression of ephrin B2 and smooth muscle actin in neovessels of Lewis Lung Carcinomas, along with low-CD36 expression or CD36 deficiency. Conclusions—: Lysophosphatidic acid/PKD-1 signaling leads to nuclear accumulation of histone deacetylase 7, where it interacts with forkhead box protein O1 to suppress endothelial CD36 transcription and mediates silencing of antiangiogenic switch, resulting in proangiogenic and proarteriogenic reprogramming. Targeting this signaling cascade could be a novel approach for ischemic cardiovascular disease and cancer. Abstract : Supplemental Digital Content is available in the text.